2023
DOI: 10.1021/cbmi.3c00002
|View full text |Cite
|
Sign up to set email alerts
|

Probing Oxidant Effects on Superoxide Dismutase 1 Oligomeric States in Live Cells Using Single-Molecule Fluorescence Anisotropy

Abstract: The protein Cu/Zn superoxide dismutase (SOD1) is known to function as a dimer, but its concentration in cells (∼50 μM) and the dimerization constant (K d of 500 μM) results suggest that it exists in a monomer-dimer equilibrium. It is unclear how the oligomeric state of SOD1 changes when cells are initially exposed to high levels of extracellular oxidative stress. To address this problem, we introduced the single-molecule fluorescence anisotropy (smFA) assay to explore SOD1 oligomeric states in live COS7 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Highlighting the power of single-molecule approaches in dynamic studies, our work contributes two new methodologies: single-molecule fluorescence anisotropy (smFA) and the single-molecule neighboring density (smND) assay. , smFA brings a new dimension to SRM by enabling the observation of intracellular viscosity through the measurement of rotational mobility of fluorescent proteins. On the other hand, the smND assay quantifies protein oligomeric states directly within cells by analyzing the spatial distribution and density of individual protein molecules . Utilizing the probability of neighbor density model, which accounts for factors like protein concentrations and photoactivation efficiency, the smND assay can distinguish between various oligomeric states by comparing experimental data against simulated distributions of protein assemblies.…”
Section: Super-resolution Microscopy: Unveiling Fine Structures and M...mentioning
confidence: 99%
“…Highlighting the power of single-molecule approaches in dynamic studies, our work contributes two new methodologies: single-molecule fluorescence anisotropy (smFA) and the single-molecule neighboring density (smND) assay. , smFA brings a new dimension to SRM by enabling the observation of intracellular viscosity through the measurement of rotational mobility of fluorescent proteins. On the other hand, the smND assay quantifies protein oligomeric states directly within cells by analyzing the spatial distribution and density of individual protein molecules . Utilizing the probability of neighbor density model, which accounts for factors like protein concentrations and photoactivation efficiency, the smND assay can distinguish between various oligomeric states by comparing experimental data against simulated distributions of protein assemblies.…”
Section: Super-resolution Microscopy: Unveiling Fine Structures and M...mentioning
confidence: 99%
“…In certain instances, the condition only becomes discernible when patients manifest evident complications, frequently resulting in the missed opportunity for an optimal diagnosis. Additionally, conventional diagnostic methods still have limitations, such as low specificity, , cumbersome processes, and notable risks. , Recently, fluorescence optical imaging and analysis techniques have played a pivotal role in early disease diagnosis, treatment, new drug development, and drug delivery, , owing to noninvasive nature, high sensitivity, and simple operation. Hence, the development of an appropriate fluorescence probe to elucidate the mechanisms, classification, and the biological and pathological functions related to diabetes and associated diseases with viscosity and polarity holds profound significance. , …”
Section: Introductionmentioning
confidence: 99%
“…Ensemble approaches, such as ensemble FRET, BiFC, FCS, and PLA, served as foundational pillars, providing insights into the predominant oligomeric states within cellular populations. However, while these methods elucidated average oligomeric states, they could often overlook molecular heterogeneity or rare oligomeric forms. To unmask this concealed diversity, single-molecule techniques like smFRET, single particle tracking, and single-molecule anisotropy were adopted. , These methods illuminated the full spectrum of oligomeric states by capturing individual protein molecules, revealing not just the dominant forms but also transient or less abundant oligomeric states.…”
Section: Introductionmentioning
confidence: 99%
“…The complex interplay of proteins coming together to form larger structuresknown as oligomerizationhas far-reaching effects on how cells function and maintain their stability. Research has consistently shown that proteins often act in their combined or “oligomeric” forms for key cellular processes, such as regulating genes and controlling enzyme activity. The behavior of these protein assemblies is not solely determined by their individual properties but is also shaped by the specific conditions within the cell. While in vitro studies provide immensely valuable information, they often fail to fully capture the true essence of protein behaviors in a cellular context. For example, they might miss the effects of changes in cellular components or neglect variables like protein concentration and post-translational modifications.…”
Section: Introductionmentioning
confidence: 99%